Bioelectrical Impedance Analysis (BIA) for the Assessment of Body Composition in Oncology: A Scoping Review - Branco, Mariana Garcia; Mateus, Carlota; Capelas, Manuel Luís; Pimenta, Nuno; Santos, Teresa; Mäkitie, Antti; Ganhão-Arranhado, Susana; Trabulo, Carolina; Ravasco, Paula (Nutrients, 2023)
Bioelectrical Impedance Analysis (BIA) is a reliable, non-invasive, objective, and cost-effective body composition assessment method, with high reproducibility. This scoping review aims to evaluate the current scientific and clinical evidence on BIA for body composition assessment in oncology patients, under active treatment. Literature search was conducted through MEDLINE, CINAHL, Scopus and Web of Science databases, following PRISMA-ScR Guidelines. Inclusion criteria comprised studies reporting the use of BIA for body composition evaluation in adults with cancer diagnosis. Studies including non-cancer pathology or only assessing nutritional status were excluded. This scoping review comprised a total of 36 studies: 25 were original studies including 18 prospective studies, six cross-sectional studies and one retrospective study and 11 were systematic reviews. Population size for the included original articles ranged from 18 to 1217 participants, comprising a total of 3015 patients with cancer with a mean baseline Body Mass Index (BMI) ranging from 20.3 to 30.0 kg/m2 and mean age ranging between 47 and 70 years. Review articles included a total of 273 studies, with a total of 78,350 participants. The current review considered studies reporting patients with head and neck cancer (HNC) (n = 8), breast cancer (BC) (n = 4), esophageal cancer (EC) (n = 2), liver cancer (n = 2), pancreatic cancer (PC) (n = 3), gastric cancer (GC) (n = 3), colorectal cancer (CRC) (n = 8), lung cancer (LC) (n = 1), skin cancer (SK) (n = 1) and multiple cancer types (n = 6). BIA is a suitable and valid method for the assessment of body composition in oncology. BIA-derived measures have shown good potential and relevant clinical value in preoperative risk evaluation, in the reduction of postoperative complications and hospital stay and as an important prognostic indicator in persons with cancer. Future research on the diagnostic value and clinical applications of BIA and BIA-derived phase angle (PhA) should be conducted in order to predict its impact on patient survival and other clinical outcomes.